Uncertainty Analysis of Roughness Profile Measurement Using the 6 Lighting Stereophotometry Method - Irawati dewi syahwir; Irwan Setiawan; Inayah Dwi Khaira (Elinvo (Electronics, Informatics, and Vocational Education), 2026)
Surface roughness characterization of gauge blocks is a critical aspect of dimensional metrology for ensuring calibration accuracy. Conventional contact-based measurements risk inducing material surface wear; hence, a precise, non-contact alternative is highly required. This study proposes a non-contact surface roughness measurement system for stainless steel standards and gauge blocks. The system utilizes computer vision-based stereophotometry equipped with an innovative six-source radial illumination configuration. This six-light design aims to overcome shadow distortion constraints while increasing the mathematical data redundancy necessary for accurate surface topography reconstruction. The study was conducted on ten steel gauge block samples for both Class 0 and Class 1 grades, with a nominal range of 1.01 mm to 1.10 mm. The experimental results show that the system can measure the average roughness Ra in the range of 1.5712 µm to 2.1994 µm for Class 0, and 2.1644 µm to 2.7875 µm for Class 1. A comprehensive uncertainty analysis was performed, incorporating a rectangular distribution for camera resolution and a triangular distribution for temperature fluctuations. The metrological evaluation yields a consistent expanded uncertainty of 0.08 m at a 95% confidence level (k=2). These findings confirm that the six-light configuration significantly enhances the reliability of the contactless measurement system, offering strong potential for precision inspection in the automotive and advanced manufacturing industries.